Phytochemical Screening and Antibacterial Activity Studies on the Crude Leaf Extract of Solanum sisymbriifolium: Traditional Ethiopian Medicinal Plant - Gebrewbet, Gebrihans Haile; Hndeya, Abadi Gebreyesus (Advanced Gut & Microbiome Research, 2023)
Ethiopians have used medicinal plants for centuries. In some cases, it is important and the only treatment source. However, these plant species have not been fully studied. In addition, society is inevitably losing knowledge of traditional medicinal plants as society adopts new lifestyles. Consequently, the objective of this research was to determine the phytochemical components and antibacterial activity of Solanum sisymbriifolium, a traditional medicinal plant used in Ethiopia to treat arthritis. Phytochemical analyses were performed on the leaf extracts to identify the bioactive constituents. The results of this study indicated that the plant contains carbohydrates, phenols, flavonoids, alkaloids, proteins, steroids, saponins, and terpenoids. Tannins and anthraquinones were absent. Alkaloids and terpenoids’ presence in the leaves of these plants is a potential bioactive for bacterial inhibitors. At optimal conditions (62°C, 72 hr, and 1 mm particle size), the maximum extraction yield is 38.538.5±1.15%. Crystals obtained from aqueous methanol extracts were subjected to FT-IR, and the compound spectrum showed a characteristic absorption band for the N-H group at 3500 cm-1 and 1700 cm-1 for the C = O group, and the medium intensity at 1236 cm-1 indicates a C-O stretching. Sharp absorption at 707 cm-1 is inductive for = C-H bending. According to agar disc diffusion tests, plant extracts of 50 mg/mL produced 14.04 mm growth inhibition zones of Bacillus subtilis. Phytochemical and antibacterial studies of Solanum sisymbriifolium indicated that the plant is a source of highly valued compounds for the preparation of medications.